Chamadas aos Dossiês 2020: (em espanhol, inglês e francês) - Szafir, Milena; Marinho, Claudia; Machado, Andreia; Lima, Nilo; Rivas, Nilo; Alfonso, Gerardo; Felix, (Revista Vazantes, 2020)
Arquivos originais divulgados em junho/2020: http://www.ppgartes.ufc.br/wp-content/uploads/2020/06/CHAMADA-Vazantes-2020-1-V1s.pdf (último acesso em 25/12/2020) http://www.ppgartes.ufc.br/wp-content/uploads/2020/06/CHAMADA-Vazantes-2020-2design1.pdf (último acesso em 25/12/2020)